The influence of the construction of tram fronts on the consequences of accidents with passenger cars - Jakub Seidl (Acta Polytechnica CTU Proceedings)
In recent years, there has been a large increase in passenger and public transport in cities. An increase in traffic flow results in an increasing risk of accidents. Manufacturers and operators of trams are increasingly subject to higher requirements for ensuring the safety of vehicles. Vehicle safety can be divided into two groups: active and passive safety. Systems and elements of active safety are intended to reduce the risk of accidents. Systems and elements of passive safety are intended to minimize the consequences of accidents. The requirements for the passive safety of newly designed railway vehicles are described in standard EN 15227. Standard EN 15227 was created due to the effort to protect passengers and crew inside railway vehicles in the event of an accident, so it is a so-called self-protection. The standard EN 15227 does not stipulate any requirements for so-called partner protection. Partner protection means an approach in which the vehicle protects passengers inside and outside the vehicle with its deformation elements. This article deals with the issue of how the construction of the front of tram vehicles designed according to the requirements of the standard EN 15227 will affect the consequences of tram´s accidents with passenger cars. The first part of the article describes the requirements of the standard EN 15227 for newly designed trams. Than it describes the creation and evaluation of tram accident statistics in the Czech Republic for the years 2016 to 2018 with regard to the types of collision vehicles, collision directions and consequences of accidents. From the results of the evaluation of the accident statistics, a collision scenario was determined, in which the passengers inside cars were most often injured. The last part of the article is devoted to the creation of simulation models of accidents of three trams with a car and evaluation of simulation calculations with regard to the risk of injury to car´s driver in an accident with trams using human biomechanical criteria.